RESEARCH-ORIENTED TEACHING IN HOSPITALITY AND TOURISM MARKETING: CRITICAL REFLECTIONS ON PRACTICE (Journal of Educational Sciences, 2020)
The article considers crucially the introduction of research approach and research training in teaching business disciplines. The development of research culture at the University and its practical and social significance among students and University employees is becoming an essential component of well-developed modern universities. Research-oriented learning strategies are considered very important not only for research universities, but also for business universities in Kazakhstan. This article provides critical reflections on professional experience of using research-oriented teaching strategies in business related disciplines and describes the process of implementation of new teaching methodologies in higher education. It presents the preliminary results of the part of a longitudinal observational study on students’ performance and professional development affected by competencybased research-focused learning on the example of «Services Marketing» course. Quantitative as well as observational data have been collected within the prolonged periods of time including 3 years of teaching experience. A comparative analysis of academic performance showed that average grades for research-based student assignments had been lower than grades for traditional academic tasks, while overall professional competences of students had been significantly improved as a result of researchoriented teaching. The study contributes to the body of knowledge describing the state of transitional educational systems in developing countries and fills a contextual gap by addressing important methodological issues of higher education in Kazakhstan.  Key words: research-oriented teaching, research methodology, competency-based learning, hospitality and tourism.